Developing Learning Communication Media in Science Education: Improving Critical Thinking and Honesty in Seventh Grade - Elif Muti'atur Rohmah; Hariyanto; Ahmad Zaki Emyus (FAKULTAS DAKWAH UIN SALATIGA, 2025)
Communication is the most important means of conveying goals; poor communication can lead to the failure of expected goals. This can also occur during the learning process at school. This study aims to enhance students' critical thinking skills and develop their honest character by utilising digital communication media. This research approach utilises R&D combined with the ADDIE model to produce a means of communication between teachers and students in the form of Google Sites learning media integrated with Canva. Experts then validated the resulting learning media to ensure strong results for use in learning. Experts also validated the critical thinking test instrument and the honest character observation sheet to ensure that strong, reliable instruments would be used. The sample of this study consisted of class VII D students of MTsN 2 Jember in the 2024/2025 academic year, who were selected using a purposive sampling technique. The data analysis technique employed N-Gain and was followed by an independent sample t-test, which was subsequently evaluated using Cohen's d test. The results showed that students' critical thinking skills increased to a high category (Cohen's d = -4.501). There was also an increase in students' character scores, which were in the high category (Cohen's d = -5.386). These results suggest that effective communication media can enhance students' critical thinking skills and character. Teacher communication with students using digital media can overcome students' learning difficulties, increase their interest and motivation to learn, and improve their critical thinking skills. Rules regarding assignments and how to monitor them in learning through the Google Sites application train students' character of honesty. Students also responded enthusiastically to the presence of this media. The fatigue they previously experienced in conventional learning was alleviated by delivering more engaging lessons with fresh themes and animations on the Canva display, integrated with Google Sites.